Teaching English using a genre pedagogy to Islamic junior high school students - Aunurrahman Aunurrahman; Any Hikmayanti; Yuliana Yuliana (Universitas Islam Negeri Palangka Raya, Indonesia, 2020)
This descriptive qualitative study aims to find out how a genre pedagogy is used to teaching the English language. A class consisted of thirty-six students of a public Islamic junior high school was selected purposefully as participants. The data collection involved participant observation, field notes, and documents, in this case, the students' works. The participant observations were conducted in four meetings. During the observations, this study collected the students